Pedestrian-induced lateral vibration of footbridge based on binary coupled Kuramoto model. Issue 8 (3rd August 2023) - Jia, Buyu; Mao, Siyi; Chen, Yuxuan; Yu, Xiaolin
Abstract: At present, inverted pendulum model (IPM) has been recognized by increasing researchers due to its capability to capture the characteristics of pedestrian lateral excitation. However, the IPM still has a downside that has been continuously questioned: the velocity proportional pedestrian load coefficient c p is inconsistent with the on-site observations in the case of pedestrian walking with normal frequency. This problem is most likely resulted from that the IPM ignores the synchronization effect. The IPM is derived from indoor single-person experiment and cannot consider the synchronization in the crowd. Synchronization effects are classified into two types： pedestrian–bridge and pedestrian–pedestrian synchronizations. Pedestrian–bridge synchronization is stimulated by bridge vibration, whereas pedestrian–pedestrian synchronization is stimulated by surrounding crowd. In this study, a novel model for pedestrian-induced lateral vibration of footbridge is proposed. It uses the IPM as the basis and adopts a binary coupled Kuramoto model that originally derived from the collective synchronization phenomena to overcome the limitation in IPM. This model can consider the pedestrian–bridge and pedestrian–pedestrian synchronizations, which provides a new way to reveal the mechanism of pedestrian-induced lateral vibration of footbridge. The proposed method is verified through a case study of the London Millennium Bridge, and some useful conclusions are obtained.